Online branding in SMEs as a strategic initiative during COVID-19 pandemic implication to revenue generation - Brosas, Kenette Joy; Cabug-os, Adrheyni Kyle; Cayaco, Rhendel Khey; Dacuyan, Flordeliz B. (Tacloban City Division of Management, University of the Philippines Visayas Tacloban College, 2022)
Micro, small and medium enterprises are one of the fundamental economic drivers on both macro and micro scales. In this context, SMEs struggle to keep their businesses afloat as the online shift accelerated when the Covid-19 pandemic struck. To increase efficiency and to continue operations, SMEs took measures to increase their revenue generation. SMEs that incorporate internet activity with theu marketing operations know the advantage of online branding and its reach. Although there has been academic literature on SMEs in the country and their responses to the pandemic's financial turmoil, studies have not yet explored SMEs in Tacloban, which may have different stimuli and pretexts for their business responses. The study involved 17 small and medium businesses in Tacloban City that actively use social media platforms. The study posits the importance of online branding in relation to SMEs and local entrepreneurs' sales and revenue generation. The research revealed that online branding, particularly the use of free and low-cost tools such as social media, aids in building market resonance and thus reaching a wider market. Hence, to determine online branding as a strategic initiative for revenue generation, it is essential to determine the effects of online branding on businesses that implement this marketing and revenue-generating strategy.
Undergraduate thesis (Bachelor of Science in Management) -- University of the Philippines, Tacloban.
Keywords: Online branding -- Tacloban City